The Law and Industrial Relations / Le droit et les relations industrielles - Rand, Justice (Relations industrielles / Industrial Relations, 1962)
SummaryIn the present article, the author outlines the new reality of modern industry; he goes on to advocate the need for new ideas and modified conceptions about labour relations as they exist in our present society. He finally points out the fact that industry must be conceived in terms of a social function.